Coal, nuclear and renewable energy policies in Germany: From the 1950s to the "Energiewende". (December 2016) - Renn, Ortwin; Marshall, Jonathan Paul
Abstract: Over the last 50 years, German energy policy has ranged from strong enthusiasm for both coal and nuclear energy to deep skepticism. The most dramatic changes with respect to energy policies have occurred as a response to nuclear accidents, yet the accidental and unintended effects of coal policies are also important in influencing the trajectory. The newly emerging climate debate prevented the coal industry from acting as a substitute for the diminishing share of nuclear power. In 2011 the conservative government announced the Energiewende ('energy transformation') and decided to reduce the amount of fossil fuels from 80% of the energy supply to 20% by 2050. However, while the verdict on nuclear was unequivocal with a final phase-out date of 2022, the share of coal in the electricity market did not decrease and the amount of carbon dioxide released into the air slightly increased from 2011 to 2013. There are growing conflicts over the immediate costs and practicalities of coal replacement. Consequently, the future of coal in Germany is still relatively open and contested. Highlights: German energy policy has ranged from enthusiasm about coal and nuclear to skepticism. Policy has been driven by protest, planning, contingency and opportunity seeking. Policy has resulted in paradoxes and unintended effects. Nuclear energy seems to be finished but coal may linger on.